Skin in the game : hidden asymmetries in daily life - Taleb, Nassim Nicholas, 1960- (Random House, 2018)
Discusses how the willingness to accept one's own risks is an essential attribute for defining what it means to understand the world, succeed in life, contribute to a fair and just society, and influence others.